ANALISIS PEMASARAN KOPI DI KECAMATAN BERMANI ULU RAYA KABUPATEN REJANG LEBONG - Sri Sugiarti (Jurnal Agrisep)
The objectives of the research are to study coffee marketing system and to analyze marketing margin in Bermani Ulu Raya district. From these objectives, marketing structure and market behaviorthat reflect a coffee marketing efficiency in Bermani Ulu Raya district can be examined. The result showed that coffee marketing system in the Bermani Ulu Raya is inefficient as indicated by small share margin at frm level and big share marketing margin at following marketing channels. The research also showed that coffee market can be categorized as olygopsonistic market especially wholesaler level.